Reporting characteristics and quality of randomized controlled trial protocols in traditional Chinese medicine: a cross-sectional study - Zhang, Lin; Li, Han; Hu, Lihan; Ou, Xiangqin; Tan, Hanzhi; Zhang, Xuanqi; Lau, Chung Tai; Lyu, Aiping; Bian, Zhaoxiang; Zhang, Xuan (Frontiers in Pharmacology, 2024)
Objectives: The impact of the Standard Protocol Items: Recommendations for Interventional Trials of Traditional Chinese Medicine (SPIRIT-TCM) Extension 2018 statement on the reporting quality of RCT protocols in Traditional Chinese Medicine (TCM) is not clear. This review aimed to assess the reporting characteristics and quality of randomized controlled trial (RCT) protocols involving interventions such as Chinese herbal medicine formulas (CHMF), acupuncture, and moxibustion published in the last three years. Methods: We conducted an extensive search among multiple databases, including All EBM Reviews, Allied and Complementary Medicine (AMED), Embase, Ovid MEDLINE(R), PubMed, Web of Science, Google Scholar, and ClinicalTrials.gov for publications in English from January 1, 2020, to August 10, 2023. Two reviewers independently assessed the eligibility of the publications, extracted predetermined information, and evaluated the reporting based on the SPIRIT-TCM Extension 2018 checklist.Results: Out of the 420 eligible protocols (comprising 163 studies on CHMF, 239 on acupuncture, and 18 on moxibustion), the average reporting compliance rate was only 35.4%. Approximately half of the assessed items fell into the category of poorly reported, demonstrating a compliance rate below 65%. Notably, reporting compliance in acupuncture and moxibustion interventional studies exhibited higher scores compared to those in CHMF studies. Conclusion: Continued, concerted, and coordinated efforts are required by journals, editors, reviewers, and investigators to improve the application and promotion of the SPIRIT-TCM Extension 2018 reporting guideline.